Extractıon of collagen from food waste and the preparatıon of polyhydroxyalkanoate composıtes - Wafula, Mathıas Wesamba (My University, 2017)
Kolajen doğada, omurgalı hayvanlarda en çok bulunan proteinlerden birisidir ve farmasötik, biyomedikal ve gıda endüstrilerinde sayısız uygulama alanlarına sahiptir.

Collagen is one of the most abundant proteins in vertebrates and has numerous uses in the fields of pharmaceutical, biomedical and food industry.
Keywords: Biyokimya; Food waste; Geri dönüşüm; Gıda atıkları; Kolajen; Material; Polihidroksialkanoat Collagen; Polyhydroxyalkanoate